Unraveling the complex burial history of the Antrim formation in Michigan basin using paleomagnetism, rock magnetism and geochemistry - Heij, Gerhard; Elmore, Richard Douglas (Frontiers in Earth Science, 2022)
This paper presents an integrated paleomagnetic, rock magnetic and geochemical study of the Devonian Antrim shale in the Michigan Basin. Specimens were obtained from two unoriented vertical cores (named St. Chester and Krocker) and sampled relative to a master specimen orientation line. Alternating field (AF) demagnetization experiments isolated a lower coercivity component (LC) from 0 to ~60mT in the Krocker core and corresponds to a Jurassic (170Ma ± 25) magnetization. Higher coercivity components (HC) in the Krocker core are unblocked from ~60 to 120 mT and unlike LC components, occasionally exhibit stable unblocking temperature ranges (e.g. 150 to 450°C) and higher AF demagnetization ranges (~60 to 120mT). HC components in the Krocker core are unique to certain members within the Antrim shale with a poorly resolved Middle Permian/Late Triassic magnetization in the Paxton member and Late Pennsylvanian (305Ma ± 10) component in the Norwood. The St. Chester well exhibited a LC component among all specimens with a slightly older (205Ma ± 10) than the Krocker core. Rock magnetic parameters indicate the magnetization resides in PSD/SD magnetite in both HC and LC components. Overall, the magnetizations are interpreted to be chemical remanent magnetizations (CRMs) with the HC component residing in SD magnetite which formed during hydrothermal activity in both cores. The LC component likely resides in PSD/MD magnetite and is interpreted to have formed in response to fluid flow associated with tectonic uplift and/or hydrocarbon migration. Petrographic observations indicate mineral assemblages consistent with hydrothermal mineralization (e.g. baroque dolomite). Depleted δ18O data from carbonate fractures are consistent with a hydrothermal fluid magnetization mechanism. Consistent anisotropy of magnetic susceptibility (AMS) lineations indicates either a long-lived paleocurrent direction or far-field tectonic shortening originating from the neighboring Acadian orogeny. Inorganic geochemistry indicate that paramagnetic Fe-rich clays carry the AMS signal. Lastly, an evaluation of the origin of chalcopyrite and monazite is performed through provenance analysis. These minerals are attributed to hydrothermal mineralization however, strong evidence suggests that some fraction of these grains were sourced from the Michigan Peninsula.